Pengaruh Kualitas Pelayanan dan Kualitas Hubungan terhadap Efektivitas Pelayanan serta Implikasinya terhadap Kepuasan Pasien Rawat Jalan (Studi Survei di RSUD Sultan Imanuddin Pangkalan Bun) - Hio, Aro Die; Djogo , Ony; Utojo, Widjadjanti; Yuliaty, Farida; Syahidin, Rukhiyat (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The suboptimal patient satisfaction is caused by the effectiveness of services that have not yet reached their maximum potential, which is influenced by both service quality and relationship quality that are still not optimal. This study aims to identify, examine, and analyze the effects of service quality and relationship quality on service effectiveness at Sultan Imanuddin Pangkalan Bun Regional General Hospital (RSUD), as well as their implications for patient satisfaction. The study uses a quantitative method by conducting a survey through the distribution of questionnaires to 271 respondents who are patients at RSUD Sultan Imanuddin Pangkalan Bun. Path analysis techniques were used to process the data and test the research hypotheses. The results of the study indicate that both service quality and relationship quality have a positive and significant effect, both partially and simultaneously, on service effectiveness. Furthermore, service effectiveness also has a positive and significant impact on patient satisfaction. The implications of this study emphasize the importance of improving service quality and relationship quality with patients in order to enhance service effectiveness at the hospital, which will ultimately increase patient satisfaction and strengthen the hospital's image and reputation.